Identification of a novel HLA‐B*54:34 allele by polymerase chain reaction sequence‐based typing in a Chinese leukemia patient. (22nd February 2016) - Han, Z.‐D.; Dong, L‐N.; Wang, W.; He, J.; Zhu, F.‐M.
Abstract : HLA‐B*54:34 is different from HLA‐A*54:01:01 by a single nucleotide substitution at position 343 G>A.